Microplastics composition and load from three wastewater treatment plants discharging into Mersin Bay, north eastern Mediterranean Sea. (January 2020) - Akarsu, Ceyhun; Kumbur, Halil; Gökdağ, Kerem; Kıdeyş, Ahmet E.; Sanchez-Vidal, Anna
Abstract: Copious quantities of microplastics enter the sewage system on a daily basis, and hence wastewater treatment plants (WWTPs) could be an important source of microplastic pollution in coastal waters. Influent and effluent discharges from three WWTPs in Mersin Bay, Turkey were sampled at monthly intervals over a one-year period during 2017. When data from all WWTPs were combined, fibers constituted the dominant particle form, accounting for 69.7% of total microplastics. Although notable oscillations in microplastic particle concentrations were observed throughout the year influent waters on average contained about 2.5-fold greater concentrations of microplastics compared to the effluent waters. An average of 0.9 microplastic particles were found per liter of effluent from the three WWTPs amounting to around 180 × 10 6 particles per day to Mersin Bay. This shows that despite their ability to remove 55–97% of microplastics, WWTPs are one of the main sources of microplastics to the northeast Mediterranean Sea. Graphical abstract: Unlabelled Image Highlights: This is the most detailed microplastic study from WWTPs in the north-eastern Mediterranean. Fibers were dominant microplastics in effluent samples. The majority of detected microplastics were >500 μm in length. Daily about 180 million microplastic particles enter Mersin Bay from the three WWTPs studied. Despite removal of majority particles, WWTPs are still a major source of microplastics pollution at sea.